The Alternations and the Semantic Components of the Verb Dre ‘Tear’ in Sorani Kurdish and its English Equivalent ‘Tear’ - Gharib, Hiba Esmail (Journal of University of Human Development, 2015)
This paper undertakes a sematic-syntactic analysis of verbs relating to the action of ‘tearing’ in Sorani Kurdish and English; it employs the framework of the Natural Semantic Metalanguage (hereafter, NSM) developed by Anna Wierzbicka and her colleagues. I will use NSM to fully investigte the meanings of the two verbs and to reveal the semantic structures and distinctive aspects of verbs under investigation. The NSM methodology, based on semantic primes and a grammar of combinability, enables the researcher to dig deep into language-specific concepts in a clear cut manner, while at the same not being a linguistic bias.